Multiple types of human papillomavirus in cervical samples in women in Campo Grande, MS, Brazil - Inês Aparecida Tozetti; Ilzia Doraci Lins Scapulatempo; Vicky Liege Kawski; Antonio Walter Ferreira; José Eduardo Levi (Brazilian Journal of Infectious Diseases)
We analyzed 87 cervical samples from Campo Grande, Mato Grosso do Sul, with a PGMY/GP+ nested PCR system. Positive samples were typed using E7 type-specific primer pairs for HPV 6/11, 16, 18, 45 and 66. Eighteen samples (22%) were infected with HPV6/11, 18 samples (22%) with HPV66, 13 samples (15.9%) with HPV45, 8 samples (9.8%) with HPV18 and 7 samples (8.5%) with HPV16. Seventeen samples (20.7%) were infected by two HPV types, and five samples (6.1%) by three HPV types. We conclude that infection with multiple types is present at a high frequency in our population and that there is a relation between some types and cytological finds.